Efficient Testing Light Path for Aspherical Surfaces Based on Secondary Imaging - Xinrui Wang; Xin Li; Quan Zhang; Wei Wei; Enchao Liu (Photonics)
At present, off-axis three-mirror optical systems mostly adopt aspherical mirrors with small apertures and small F/# to meet the development requirements of remote sensing payloads towards high precision, small volume, and lightweight design. However, current references rarely provide the derivation, design, and detection of the testing light path for aspherical mirrors with small apertures and small F/#. Aiming at the existing gap, this paper proposes a method of decomposing the compensation optical path into two imaging light paths and derives the initial structure of the compensation optical path. Furthermore, specific solutions are proposed from two aspects: the design of the null compensator and the establishment of the testing light path. Finally, the compensation optical path design and detection are carried out for the primary mirror and the tertiary mirror of the self-calibrating real entrance pupil imaging spectrometer, guiding the completion of the system processing, assembly, and adjustment. The detection results show that the RMS of the surface shapes of the primary mirror and the tertiary mirror is 1/40λ (λ = 633 nm). This derivation method and the design method of the initial optical path have the characteristics of simple calculation, rapid optimization, and universal applicability, and are applicable to the detection of all quadratic concave surfaces.